Slavery and Absolutism in Locke’s Two Treatises: A Response to Olsthoorn and van Apeldoorn - Waldmann, Felix (Locke Studies, 2021)
The following Note responds to a recent article by Johan Olsthoorn and Laurens van Apeldoorn on slavery and political absolutism in Locke’s Two Treatises of Government. The Note engages with Olsthoorn and Apeldoorn’s important article but queries its principal contentions.